Dakhîl al-Isrâ’ilîyât Kisah Nabi Yûsuf dalam al-Jâmi‘ li Ahkâm al-Qur’ân Karya al-Qurtubî - Amrullah Hafizh, Azhar (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2015)
Normatively, the Prophet Muhammad is not giving a ban to tell tales originating from the Banî Isrâ’îl. The Prophet simply gave the record that his people did not justify and deny the stories narrated by Ahl al-Kitâb. However, in the course of the history of Islam, many isrâ’ilîyât seeps into some sort of authoritative books of Jâmi‘ al-Bayân created by al-Tabarî, Tafsîr al-Qur’ân al-‘Azîm by Ibn Kathîr, Rûh al-Ma‘ânî by al-Alûsî, and al-Jâmi‘ li Ahkâm al-Qur’ân by al-Qurtubî. Ironically, in many cases, isrâ’ilîyât that goes into the book of commentary of the Koran without any comments from the authors, so it assumes that the isrâ’ilîyât is a strong opinion and can be used as a reference. As a result, isrâ’ilîyât like virus that continues to undermine the authenticity of the Koran